First Experience of Patent Ductus Arteriosus Stenting in Neonate with Pulmonary Atresia and Intact Ventricular Septum in North Sulawesi, Indonesia - David S. Waworuntu; Claresta Claresta (e-CliniC, 2023)
Abstract: Stenting of patent ductus arteriosus (PDA) is a minimally invasive catheter-based temporary palliative procedure, and it serves as an alternative to surgical shunt in neonates with duct dependent pulmonary perfusion, such as pulmonary atresia. This presentation aimed to report the first experience of PDA stenting in a neonate with pulmonary atresia in North Sulawesi, Indonesia. We reported a female neonate patient, weighing 3775 grams, referred from primary hospital with suspect congenital heart disease. The patient was born at 40 weeks of gestational age by caesarean section delivery from a primigravid mother aged 23 years with inertia uteri and strangulation of nuchal cord. At birth, she cried immediately and her APGAR score was 6-7. On her first day of life, she looked cyanotic, therefore she was referred to Prof. Dr. R. D. Kandou Hospital. Physical examination showed that she had perioral cyanotic and peripheral cyanotic with SpO2 58%. Chest X-ray showed cardiomegaly. Echocardiography revealed pulmonary atresia with PDA with intact ventricular septum. PDA stenting was done on her second day of admission. After the procedure, she was clinically stable with SpO2 80%, and was treated with intravenous antibiotic, and intravenous heparin and aspirin enterally. On the third day post procedure, she was discharged and no complication was found. PDA stenting in patient with duct-dependent pulmonary circulation appeared to be an alternative to surgery. It provided bridging palliation until the time of definitive surgery. The effectiveness of the procedure was highlighted by the fact that all the patients showed significant improvement in arterial saturation and pulmonary vascular marking. In conclusion, PDA stenting is considered feasible, safe and associated with lower mortality rates and shorter hospital length of stay than systemic-pulmonary surgical shunt procedure. Early detection and timely management are imperative to save the life. Keywords: patent ductus arteriosus stenting; pulmonary atresia